Characterization of Hot-Wire Detonators Using Analytical Modeling and Computational Tools - Lambrecht, M.; Baum, C.; Schamiloglu, E.; Cartwright, K. (2008 DoD High Performance Computing Modernization Program Users Group Conference, 2008)
An effort is underway to determine the electromagnetic (EM) characteristics of hot-wire detonators to quantify the possible effects of EM radiation. The analyses include a comprehensive investigation of physical detonator characteristics, which is then used to model detonators using EM theory and numerical simulations. The theoretical analysis treats the detonator as a cascaded transmission line incorporating several different dielectric regions, and examines both differential and common mode excitation. In addition, the detonator is modeled and simulated using ICEPIC (Improved Concurrent electromagnetic particle in cell), a finite-difference-time-domain (FDTD) EM solver. The cascaded transmission line model is then augmented with additional circuit elements whose values are found using ICEPIC. This combination produces a refined transmission line model that is implemented in MATLAB and can be run quickly for a wide range of detonators to determine possible deviations in radio frequency (RF) response due to manufacturing variations. A detailed RF response is not a given specification for detonators and, therefore, it is not a characteristic that is controlled during manufacturing. The results of both the analytic and computational methods, including detonator input impedance and resonant frequencies, are compared.